1997
DOI: 10.1021/ja9722685
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 1,2-Bisketenes from Cyclobutene-1,2-diones by Flash Photolysis and Ring Closure Kinetics1a

Abstract: The interconversion of cyclobutene-1,2-diones (1) and 1,2-bisketenes (RCCO)2 (2) has been surveyed for different combinations of substituents R = H, Me, t-Bu, Ph, Me3Si, CN, Cl, Br, R1O, alkynyl, and PhS. The bisketenes 2 have been generated by flash photolysis, and the kinetics of their conversion to 1 have been studied by time-resolved infrared and ultraviolet spectroscopy. The rate constants of the ring closure of 2 are correlated by the ketene stabilization parameters (SE) and with calculated barriers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…The strong band observed at 2110 cm −1 is assigned to ketene 3a in good agreement with previous studies on α-diazo ketones 52,53,54,55 such as α-diazo- p -methoxyacetophenone (2115 cm −1 ) and α-diazoacetophenone (2118 cm −1 ). 52 …”
Section: Resultssupporting
confidence: 91%
“…The strong band observed at 2110 cm −1 is assigned to ketene 3a in good agreement with previous studies on α-diazo ketones 52,53,54,55 such as α-diazo- p -methoxyacetophenone (2115 cm −1 ) and α-diazoacetophenone (2118 cm −1 ). 52 …”
Section: Resultssupporting
confidence: 91%
“…Squaramide motifs are a class of interesting photoresponsive species that can be converted into their corresponding bisketenes (Scheme ). Although this process is thermally reversible in non-nucleophilic solvents and under inert atmosphere, bisketenes undergo irreversible reactions with H 2 O in usual biological media, thereby preventing ring closure to recover the initial squaramide motif …”
Section: Introductionmentioning
confidence: 99%
“…DCP is produced together with CO, and results from decarbonylation of the bisketene, probably involving intermediacy of the ketenylcarbene. 23 The DFT(B3LYP)/6-311++G(d,p) calculations indicated that the trans-trans conformer of DCP should be more stable than the cis-trans form by 3.42 kJ mol -1 (3.59 kJ mol -1 , if zeropoint vibrational energy correction is considered). The spectroscopic data indicate that, at the end of the UV-irradiation, the two conformers are present in the matrix in a proportion that is equal to the degeneracy of the conformational level (1 for the trans-trans conformer and 2 for the cis-trans form).…”
Section: Irradiation Of the Matrixes (Photochemistry Experiments)mentioning
confidence: 99%
“…15 Since that time, this reaction has been used to generate 1,2-bisketenes, but usually these species have only been observed at low temperature, often in matrixes, because of their facile thermal ring closure. [16][17][18][19][20][21][22][23] Observation of deltic acid (C 3 O 3 H 2 ; 2,3dihydroxycycloprop-2-en-1-one) as a photoproduct generated from squaric acid was also reported. 22,23 Maier and Rohr 22 noticed that the deltic acid, produced by irradiation of the matrixisolated squaric acid, gives rise to at least two bands owing to OH stretching vibrations (νOH), whereas the trans-trans conformer of this compound should give rise to only one infrared-active νOH band.…”
Section: Introductionmentioning
confidence: 99%